What is functional mix? An assemblage approach. (3rd April 2017) - Dovey, Kim; Pafka, Elek
Abstract: Functional or land-use mix has been seminal to urban design and planning for over 50 years. Mixed-use reduces the need for travel, increases walkability and generates street-life intensity. In this paper we review existing methods of measuring functional mix and rethink the ways in which it might be conceived, measured and mapped within a framework of assemblage thinking. We suggest a live/work/visit triangle as a promising method with a focus on the interconnections between functions rather than functions in themselves. Mapping techniques are developed to reveal the ways functional mix changes at different scales from streetscape to walkable neighbourhood. This approach is tested on detailed floor area databases from the cities of New York, Barcelona and Bogotá. Rather than reducing mix to an index, such mapping reveals each city as a mix of different mixes. These maps can be understood as urban X-rays that enable interpretation and diagnosis of urban functional mix.